2023
DOI: 10.3390/microorganisms11030813
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Reverse Purification DNA Extraction Approaches to Identify Microbial Pathogens in Wastewater

Abstract: Wastewater monitoring became a promising solution in the early detection of outbreaks. Despite the achievements in the identification of pathogens in wastewater using real-time PCR, there is still a lack of reliable rapid nucleic acid extraction protocols. Therefore, in this study, samples were subjected to alkali, proteinase K and/or bead-beating followed by reverse purification magnetic beads-based separation. Wastewater samples spiked with S. aureus, E. coli and C. parvum were used as examples for Gram-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Results of real-time PCR showed that bead beating was crucial to break the thick, homogeneous cell wall of the Gram-positive bacterium S. aureus. , In the case of E. coli, the thin cell wall could be damaged by all procedures, and no significant variation in extraction efficacy was detected .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of real-time PCR showed that bead beating was crucial to break the thick, homogeneous cell wall of the Gram-positive bacterium S. aureus. , In the case of E. coli, the thin cell wall could be damaged by all procedures, and no significant variation in extraction efficacy was detected .…”
Section: Discussionmentioning
confidence: 99%
“…For the assessment of an appropriate extraction method, different buffer and pretreatment options were tested in both real-time PCR and nanopore sequencing. 21 An overview of all of the evaluated extraction procedures can be found in Table 1. For extraction (I), the protocol of the SwiftXDNA kit (Xpedite Diagnostics GmbH, Hallbergmoos, Germany) was applied.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations